Approximating Characteristics of the Classes $L_{β,p}^{ψ}$ of Periodic Functions in the Space $L_q$ - Shkapa, V. V.; Шкапа, В. В. (Institute of Mathematics, NAS of Ukraine, 2015)
We obtain the exact-order estimates of the best $m$-term and orthogonal trigonometric approximations and establish the order of trigonometric widths for the classes $L_{β,p}^{ψ}$ in the space $L_q$ for some relations between the parameters $p$ and $q$.